SOSIALISASI BIJAK BERMEDIA SOSIAL DAN PENCEGAHAN DAMPAK PORNOGRAFI PADA REMAJA DAN PEMUDA DI DESA KARANGGULI, KECAMATAN PULAU PULAU ARU, KABUPATEN KEPULAUAN ARU - Piter Arson Welay; Ribka Djamanmona (CV. Denasya Smart Publisher, 2026)
Low levels of digital literacy among rural adolescents and youth leave them vulnerable to exposure to pornography, which can harm their psychosocial development. This community service initiative aimed to raise awareness and understanding regarding the wise use of social media and the dangers of pornography among adolescents and youth in Karangguli Village, Pulau-Pulau Aru District, Aru Islands Regency. The program employed interactive outreach, small-group discussions, and simulations on rejecting negative content, involving 13 local adolescents and youths in September 2025. Evaluation was conducted through participant observation and verbal reflection. The results demonstrated increased understanding, evidenced by the participants' ability to identify harmful content and formulate assertive refusals, as well as the establishment of a shared commitment to maintaining a healthy digital environment. This activity serves as an initial step toward fostering community-based digital resilience in island villages.